Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPA dengan Menggunakan Pendekatan Saintifik di Kelas V SDN 15 Batang Gasan Kabupaten Padang Pariaman - Rahmiyanti Rahmiyanti; Muhammadi Muhammadi; Tin Indrawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research is motivated by the low learning outcomes in grade V SDN 15 Batang Gasan, Padang Pariaman Regency. This is because in learning many students are not active in learning, so the learning outcomes obtained under the Shiva Completion Criteria (KKM) are 70. To overcome these problems a scientific approach is used. The purpose of this study is to improve student learning outcomes in science learning.The approach used is a qualitative and quantitative approach. This type of research is classroom action research (CAR). This research was conducted in the second semester of the 2014/2015 academic year. This research includes: 1) planning, 2) implementation, 3) observation, and 4) reflection. Sujek research consisted of teachers and fifth grade students at SDN 15 Batang Gasan, Padang Pariaman District, totaling 16 students.The results of the study in the study of RPP for the first cycle scored 73.22% while in the second cycle the assessment of the RPP got a score of 87.50%. The implementation phase of the teacher aspect in the first cycle scored 66.07%, increasing in the second cycle to 87.50%. The implementation phase of the aspects of students in the first cycle scored 62.50%, increasing in the second cycle to 85.71%. The activity of students in cycle I got a score of 60%, increasing in cycle II to 85%. Student learning outcomes in the first cycle scored 71.37, increased in the second cycle 84.50. It can be concluded that the scientific approach can improve science learning outcomes in grade V SDN 15 Batang Gasan, Padang Pariaman Regency.